2020
DOI: 10.3389/fgene.2020.556267
|View full text |Cite
|
Sign up to set email alerts
|

Genome Complexity Reduction High-Throughput Genome Sequencing of Green Iguana (Iguana iguana) Reveal a Paradigm Shift in Understanding Sex-Chromosomal Linkages on Homomorphic X and Y Sex Chromosomes

Abstract: The majority of lizards classified in the superfamily Iguanoidea have an XX/XY sexdetermination system in which sex-chromosomal linkage shows homology with chicken (Gallus gallus) chromosome 15 (GGA15). However, the genomics of sex chromosomes remain largely unexplored owing to the presence of homomorphic sex chromosomes in majority of the species. Recent advances in high-throughput genome complexity reduction sequencing provide an effective approach to the identification of sexspecific loci with both single-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 99 publications
0
43
0
Order By: Relevance
“…The molecular machinery of the sex determination pathway is observed across ESD amniote lineages, which concurs with independent co-option of the same epigenetic process [59]. Interestingly, recent comparative genomic analyses indicate that the majority of the squamate reptile chromosome 2 (SR2) and the snake W sex chromosomes share partial sex chromosomal linkage homologies with sex-related elements of other amniotes, despite their apparent diversity of sex-determining mechanisms [18,25,27,28,[30][31][32]58]. Hypothetically, the SR2 and snake W sex chromosomes may have been part of a larger ancestral amniote super-sex chromosome with a GSD system that subsequently split into many sex chromosomes across several amniote lineages by multiple chromosomal rearrangements such as fission [27,28,30].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The molecular machinery of the sex determination pathway is observed across ESD amniote lineages, which concurs with independent co-option of the same epigenetic process [59]. Interestingly, recent comparative genomic analyses indicate that the majority of the squamate reptile chromosome 2 (SR2) and the snake W sex chromosomes share partial sex chromosomal linkage homologies with sex-related elements of other amniotes, despite their apparent diversity of sex-determining mechanisms [18,25,27,28,[30][31][32]58]. Hypothetically, the SR2 and snake W sex chromosomes may have been part of a larger ancestral amniote super-sex chromosome with a GSD system that subsequently split into many sex chromosomes across several amniote lineages by multiple chromosomal rearrangements such as fission [27,28,30].…”
Section: Introductionmentioning
confidence: 80%
“…Sex chromosomes evolved independently multiple times within amniotes and remained notably stable after their emergence in mammals, birds, and many lineages of reptiles [16][17][18]56,57]. This scenario is supported by evidence of the same linkage homology blocks that perform the role of sex chromosomes in several amniote lineages, or by unrelated sex chromosomes sharing partial linkage homologies across distantly related groups [18,25,27,28,[30][31][32]58]. This was probably caused by multiple random selections from a limited number of linkage homologies, or a stronger tendency for a linkage homology to be co-opted owing to its gene content, particularly as a result of enrichment of the genes involved in gonad differentiation, and the possibility of homologous sex-determining systems [7].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although transposable elements can be dispersed on many chromosomes or even throughout the entire genome, large amplification of the elements are often found on sex chromosomes in many organisms ( Ahmad et al, 2020 ; Koomgun et al, 2020 ; Laopichienpong et al, 2020 ; Yoshido et al, 2020 ). The presence of accumulated TEs leads to the establishment of heterochromatin, and possibly also to TE recombination between non-homologous copies.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the XX/XY sex determination system might co-exist with ZZ/ZW system in the same individuals of C. gariepinus. Genomic convergence has been detected by comparative cytogenetics studies in which unrelated sex chromosomes share sex chromosomal linkage homologies across distantly related species (Srikulnath et al, 2014(Srikulnath et al, , 2015Ahmad et al, 2020;Koomgun et al, 2020;Laopichienpong et al, 2020;Singchat et al, 2020a,b). We found that a male-linked locus under the 70:30 criterion shared partial homology with ADD3 which is localized on GGA6, which is further orthologous to sex chromosomes of sand lizard (Lacerta agilis).…”
Section: Discussionmentioning
confidence: 99%